A rare case of complete hydatidiform mole with a live fetus: a case report - Nagamuthu, Ezhil Arasi; Bollipogu, Srilatha; Fatima, Syeda Sumaiya; Mudavath, Padmavathy (International Journal of Research in Medical Sciences, 2017)
Twin pregnancy with complete hydatidiform mole represents a very rare obstetric problem resulting in a healthy take-home baby with only 56 cases documented in detail in literature. The main issue is to differentiate between two diagnoses: dichorionic twin pregnancy with normal fetus (46 chromosomes, 23 maternal and 23 paternal) and complete molar pregnancy (46 chromosomes, all paternal) and singleton pregnancy consisting of a triploid fetus with partial hydatidiform mole placenta (69 chromosomes, 23 maternal and 46 paternal). Management of such cases is always problematic because the possibility of fetal survival should always be weighed against the risk of complications of molar pregnancy. The specimen was received for histopathological examination and fixed in 10% formalin for processing. After gross analysis representative sections were given for tissue processing. Sections were processed routinely with paraffin embedding and stained with haematoxylin and eosin. In the present report a case of 25-year-old woman who presented to the center referred from peripheral center with 27 weeks of gestation, diagnosed as twin pregnancy with molar pregnancy and single live fetus.